Photocatalytic Properties of Office-Paper-Waste-Derived Activated Carbon for Efficient Degradation of Organic Pollutants - Ana Varadi; Adriana Popa; Dana Toloman; Cristian Leostean; Ioana Perhaiţă; Monica Dan; Arpad Mihai Rostas; Septimiu Tripon; Sergiu Macavei; Maria Stefan (Inorganics)
Sustainable waste recycling continues to be one of the most significant challenges in this century, especially for the office paper sector. On top of that, photocatalysis depends on solar radiation as an unlimited and environmentally friendly energy source for removing organic pollutants from contaminated water. The obtaining of AC from office paper waste was carried out with the help of the chemical activation method using ZnCl2 as an activation agent, followed by heating the samples in adequate conditions. In the present research, we assessed the influence of the amount of ZnCl2 activator on the properties of AC. In our experimental conditions, a part of ZnCl2 was transformed into ZnO, deposited onto AC, and formed a composite. We attempted to minimize aggressive chemical agents through inexpensive technical solutions and experimental approaches. The properties of the obtained AC samples were evaluated by XRD, XPS, SEM/EDX, EPR, and surface area and porosity investigations. All of the samples exhibit photocatalytic activity toward Rhodamine B. The photocatalytic mechanism was evaluated considering the existence of reactive oxygen species (ROSs), as evidenced by spin-trapping experiments.